Konsep Kesehatan Reproduksi Perempuan dalam al-Qur’an - Dewi, Ratna (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2019)
The purpose of this study is to find out the verses of the Qur'an related to women's reproductive health, as well as the contextual interpretation of the commentators, so that it can be seen that the Qur'an is concerned with the reproductive health of women. The concept of reproductive health of women according to the Koran consists of six concepts, namely: Menstruation (Menstruation), sex and sexuality, pregnancy, childbirth, breastfeeding, and child care. All of these concepts are taken from the explanation of the Qur'an and so in the contextual interpretation of the commentators. The results of this study conclude that the commentators have a broad understanding relating to the science of reproductive health of women. Like menstruation, about menstrual blood described in the Surah Al-Baqarah verse: 222. Then the concept of the prohibition of adultery in Islam contained in Surah al-Isro 'verse: 32. Pregnancy, verses of the Qur'an that explain about pregnancy very much, among them, Al-Qur'an Surat Al-Mukminun verses 12-14. Childbirth, Al-Qur'an explains the verse about childbirth contained in the Surah Al-Ahqaf verse 15. Breastfeeding, Breastfeeding is also a function of reproduction. Verses that explain about breastfeeding include Surah Al-Baqarat verse 233. And caring for children, as Allah SWT says in the Qur'an is related to the care of children Lukman verse verse: 13.